New sites of Taraxacum portentosum Kirschner & Štěpánek and Taraxacum vindobonense Soest against a background of their distribution in Poland - Marciniuk, Jolanta; Marciniuk, Paweł (Biodiversity: Research and Conservation, 2006)
In the paper the new sites of Taraxacum portentosum Kirschner & Štěpánek and Taraxacum vindobonense Soest are presented against a background of the current knowledge about the distribution of these species in Poland and Europe. A complete register of the sites is presented as well as the distribution maps of these species in the net of the ATPOL squares in Poland. The most important diagnostic characteristics distinguishing one species from the other are given.